2022
DOI: 10.3389/fphar.2022.877706
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Novel PGK1 Activators as Apoptotic Inhibiting and Neuroprotective Agents

Abstract: Stroke is the second leading cause of death worldwide and the leading cause of long-term disability that seriously endangers health and quality of human life. Tissue-type fibrinogen activator is currently the only drug approved by FDA for the treatment of ischemic stroke. Neuroprotection is theoretically a common strategy for the treatment of both ischemic and hemorrhagic stroke; therefore, the development of neuroprotective agent has been the focus of research. However, no ideal neuroprotective drug is clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…One study indicated that many glycolytic enzymes are repressed in astrocytes treated with I/R [ 45 ]. Novel drugs aimed at enhancing astrocytic glycolysis appear to be neuroprotective against reperfusion injury after ischemic stroke [ 46 , 47 ]. The development of new approaches to restore glycolytic flux may amplify the neuroprotective effects of glycophagy-liberated glucose on astrocytes by transforming astrocytic glucose metabolism to a more balanced state.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that many glycolytic enzymes are repressed in astrocytes treated with I/R [ 45 ]. Novel drugs aimed at enhancing astrocytic glycolysis appear to be neuroprotective against reperfusion injury after ischemic stroke [ 46 , 47 ]. The development of new approaches to restore glycolytic flux may amplify the neuroprotective effects of glycophagy-liberated glucose on astrocytes by transforming astrocytic glucose metabolism to a more balanced state.…”
Section: Discussionmentioning
confidence: 99%